Peran Citra Merek dan Brand Awareness dalam Meningkatkan Kepuasan Konsumen Produk Komestik Halal Di Kota Bogor - Fanya Dina Angraini; Erny Amriani Asmin; Tini Kartini (Universitas Muhammadiyah Palembang, 2025)
Purpose– This study aims to examine how brand image and brand awareness influence consumer satisfaction with halal cosmetic products in the city of Bogor. Design/methodology– The sort of research used is descriptive and associative studies with a quantitative technique. The records in this take a look at had been received from primary information thru questionnaires distributed to one hundred respondents who are purchasers of halal cosmetic merchandise in Bogor city. The sampling method used was purposive sampling, even as the information evaluation approach hired a couple of linear regression evaluation with the assist of SPSS version 25 software. Findings - Brand image has a positive and significant influence on customer satisfaction, and brand awareness also has a good and significant influence on buyer satisfaction, according to the results of the study concurrently, citra merek and emblem attention have a large impact on client pride with halal cosmetic merchandise in Bogor city. This indicates that a stronger citra merek and better brand awareness can improve consumer delight inside the halal cosmetics industry.